O poder das bolhas: a gaiola de ouro do Facebook - Nóbrega, Iara Mariana de Farias (Universidade Federal Rural do Semi-Árido, 2019)
This work of dissertation brings and understands the process of production and feedback of symbolic violence through internet networks, but it is a social network of Facebook. The problem studied was based on a perspective of the interdisciplinary field through the dialogue of different knowledge. To base the problem in the issue, make the status of the heritage have been central to the theory by theory by Bourdieu. To point out the process of development of Communication and Information Technologies. Relate the concept of symbolic violence and how it is expressed through the formation of mechanisms, as it was called "bubbles on the internet".Still, to bring this discussion, we will use our analysis, a fanpage "Political Pragmatism" www.facebook.com/PragmatismoPolitico as the objective to throw a look at the phenomenon of social representations based on Moscovici (2007) from the posts with a bias political. The results are verbal variables that potentiate an interaction between tastings, comments and shares, consequently, enlarging a bubble and reproducing the violent discourse in it
Keywords: Violência simbólica; Facebook; Pragmatismo político; Symbolic violence; Facebook; Bubbles on the internet; MULTIDISCIPLINAR::INTERDISCIPLINAR::COGNIÇÃO, TECNOLOGIAS E INSTITUIÇÕES